Educación en enfermería en una Universidad Pública - Urbina Rojas, Yrene Esperanza (2009)
The objective of this research was to analyze the paradigms and principles used in nursing education in the National University of Tumbes. The theoretical support was based on the main concepts in Education by FREIRE (1994, 1999, 2000, 2002); main concepts in higher education by DEMO (1998, 2002, 2004); main concepts in nursing care by WALDO (2004, 2005, 2006). The creative and sensitive method by CABRAL (1997, 1998) was used; and the Calendar Dynamics, developed in five meetings: two meetings with students and graduates, and one meeting with professors; so there were 31 participants. For the data analysis, principles of speech analysis by ORLANDI (2002) were used. The first paradigm category in education has come up from these speeches. Three topics were found on the paradigm conception of the students, graduates and professors; and, as a second category, the principles from the students, graduates and professors’ conception.